"We're stronger if we work together": experiences of naturally occurring peer support in an inpatient setting. (4th July 2019) - Galloway, Anna; Pistrang, Nancy
Abstract: Background: Research on peer support in mental health inpatient settings has focussed on formalised programmes. Naturally occurring peer support – spontaneous interactions without structure or roles – has received little attention. Aims: This study aimed to provide a detailed picture of service-users' experiences of giving and receiving support in an acute inpatient setting, and possible challenges encountered in such interactions. Staff perceptions were obtained in order to provide another perspective. Method: Twelve service-users and seven staff took part in semi-structured interviews. Braun and Clarke's method of thematic analysis was used to analyse the transcripts. Results: Service-users described a range of supportive interactions that were highly valued; themes included "Responding to distress", "Talking about personal stuff" and "We're stronger if we work together". They also described challenges and barriers, such as having to "tread carefully" and "personal difficulties", which made it difficult to engage in giving and receiving peer support. Staff accounts were broadly consistent with those of service-users, but showed less understanding of the nature of peer support and emphasised its risks. Conclusions: Naturally occurring peer support should be a recognised aspect of an inpatient stay. Staff education and policy should focus on creating environments for it to flourish.